Nilai Hematokrit pada Pasien Diare - Aulia Prameswari Hayuning Putri (Jaringan Laboratorium Medis, 2021)
Diarrhea is the passage of abnormal or watery stools that are more frequent than usual, and can be caused by infection or non-infection. Complications can occur including dehydration in patients with acute diarrhea. In cases of severe dehydration, hematological tests in diarrheal patients may be elevated, such as hematocrit and hemoglobin values. The purpose of this study was to determine the hematocrit value in inpatient diarrhea patients at the Tonjong Public Health Center, Brebes Regency. This type of research is a descriptive study using secondary data from medical record data as many as 30 respondents at the Tonjong Public Health Center, Brebes Regency. The results showed that there were 3 men who had decreased hematocrit levels and 8 people who had normal hematocrit levels. Whereas. on. In women, the hematocrit level decreased as much as. 17 people and 2 people who have normal hematocrit levels. Based on the age category, the most are the late elderly as many as 8 people and the final adults as much as 2 people. Meanwhile, based on the status of dehydration, all diarrhea patients who came for treatment at the Tonjong Health Center, Brebes Regency, 100% did not experience diarrhea with dehydration. The hematocrit levels in diarrhea patients at the Tonjong Public Health Center, Brebes Regency were 30 samples, on average they had low hematocrit levels.